THE ICONOGRAPHY OF KALA-BHAIRAVA - Genevieve (Journal of Dharma, 1977)
One of the temples of Begur, near Bangalore, is dedicated to the [jyotirlinga, known in the popular tradition as the temple of Nageshwara, the "Lord of snakes", namely, Siva. ]yo.tirlinga is one of the creative symbols of Siva meaning "fiery energy". Siva is the Lord of the fundamental elements (bbiita) such as earth (prtboi), water (apas), fire (tejas), air (vayu) and ether (akas). Consequently, this ancient Dravidian style temple has five inde- pendent sanctuaries (garbhagrahas) dedicated to each of the five elements in their "linga form". This temple was built during the early Chola period when the strategic road linking Tamilnadu to its Kamataka Province passed through Begur. The most interest- ing images of this temple were later removed to the Bangalore Museum. One of them, very striking in its iconographic details of the Dravidian style of sculpture, carries the caption, "Kala- Bhairava-Dravidian style, 10th century A.D." This icon is believed to be the original one, its replica being placed in the main sanctuary (antardla) of the temple. There is something mysterious about the Kala-Bhairava icon which seems to be unique in many ways.